Idealna žena Alkestida - Sunčič, Maja (Monitor ISH, 2003)
'The ideal wife Alcestis': Reading of different versions of the Alcestis myth allows us to contextualize the representations of the idela wife over a long period of time. In all versions of the myth, from the brief mention in Iliad to Fulgentius and Alcestis Barcinonensis in the late antiquity, Alcestis is represented as an ideal wife and a model of a woman any man would desire. The motiv of female self-sacrifice for her husband serves as the mirror of male fantasies where masculine virtue is verified through the self-deconstruction of his own wife. By sacrificing herself Alcestis not only proves her own virtue, but primarily the value of the man for whom she is sacrificing.
Keywords: Alkestida; Ancient Greek literature; antični miti; antika; classical antiquity; grška književnost; položaj žensk; samožrtvovanje; woman; ženske